Comparison of irrigant penetration up to working length and into simulated lateral canals using various irrigating techniques. (2nd April 2013) - Spoorthy, E.; Velmurugan, N.; Ballal, S.; Nandini, S.
Abstract Aim To evaluate the effect of an apical negative pressure system, a passive ultrasonic irrigation system and a combination of both apical negative pressure and passive ultrasonic irrigation on the penetration of the irrigating contrast solution (ICS) up to working length and into simulated lateral canals. Methodology The root canals of 64 single‐rooted teeth were instrumented using the ProTaper rotary system. In each sample, three simulated lateral canals were created at 2, 4 and 6 mm levels from the root apex using a 06‐size C+ file (Dentsply Maillefer, Ballaigues, Switzerland). Samples were randomly assigned into 4 experimental groups (n = 16): group I ‐ conventional needle irrigation, group II ‐ passive ultrasonic irrigation, group III ‐ apical negative irrigation system and group IV ‐ combination of passive ultrasonic irrigation and apical negative pressure irrigation system. To examine irrigating solution penetration, Indian ink was mixed with 5.25% NaOCl and delivered into the root canals. Samples were then assessed by direct observation of the images taken using Canon EOS rebel T3. The depth of penetration of ICS up to the working length and into the simulated lateral canals was analysed using chi‐squared tests. Results The combination (ANP and PUI) and ANP group had significantly deeper ICS penetration up to the working length (P < 0.001). The combination (ANP and PUI) and the PUI group exhibited significantly greater ICS penetration into lateral canals at the 6 mm level (P < 0.001). At the 4 and 2 mm levels, the combination of ANP and PUI had significantly greater ICS penetration into the lateral canals than the other groups (P < 0.001). Conclusions The combination of ANP and PUI was the only group able to achieve irrigating contrast solution penetration both up to the working length and into lateral canals.